2020
DOI: 10.1101/2020.12.18.423429
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rotavirus Replication Factories Are Complex Ribonucleoprotein Condensates

Abstract: RNA viruses induce formation of subcellular organelles that provide microenvironments conducive to their replication. Here we show that replication factories of rotaviruses represent protein-RNA condensates that are formed via liquid-liquid phase separation. We demonstrate that rotavirus proteins NSP5 and NSP2 undergo phase separation in vitro and form RNA-rich condensates in vivo that can be reversibly dissolved by aliphatic diols. During infection, these RNA-protein condensates became less dynamic and imperv… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 101 publications
(152 reference statements)
2
16
0
Order By: Relevance
“…Rotavirus replication factories, or viroplasms, have long been known as membrane-less organelles that emerge in the cytoplasm shortly after infection 12 . Our recent findings have revealed that these viral organelles are formed via liquid-liquid phase separation (LLPS) of the RV RNA-binding proteins NSP2 and NSP5 17 . Similar liquidlike membrane-less RNP condensates are ubiquitous in cells 42,[44][45][46][47] ; however, each specific type of an RNP condensate being unique in their protein and RNA composition that can be dynamically modulated by various processes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Rotavirus replication factories, or viroplasms, have long been known as membrane-less organelles that emerge in the cytoplasm shortly after infection 12 . Our recent findings have revealed that these viral organelles are formed via liquid-liquid phase separation (LLPS) of the RV RNA-binding proteins NSP2 and NSP5 17 . Similar liquidlike membrane-less RNP condensates are ubiquitous in cells 42,[44][45][46][47] ; however, each specific type of an RNP condensate being unique in their protein and RNA composition that can be dynamically modulated by various processes.…”
Section: Discussionmentioning
confidence: 99%
“…In order to monitor rotavirus transcription during the course of infection, we took advantage of the MA104 cell line stably expressing an EGFP-tagged NSP5 that readily partitions into the viroplasmic condensates 18,31,32 . At a multiplicity of infection (MOI) of 10, NSP5-EGFP-tagged granules were readily detected as soon as 2-3 hours post infection (hpi) ( Fig.…”
Section: Nsp5-egfp-tagged Viral Condensates Retain Viral Transcriptsmentioning
confidence: 99%
See 3 more Smart Citations